Non-invasive rust detection of steel plates determined through interfacial modulus - Patel, Dipen; Bhimavarapu, Yagna Valkya Reddy; Jena, Akash K.; Tadmor, Rafael; Cai, Tianxing (Frontiers in Chemical Engineering, 2023)
Initial methods to detect rust in pipelines have been conducted through invasive probes and sectioning off parts of the facility as the plant is running. These methods greatly increase the costs overall. The need for a feasible solution to this issue lies in the detection of rust formation through a non-invasive method. This study’s objective is to measure rust formation through droplet motion on the outer layer of pipelines. Multiple experiments are conducted using carbon steel sheets whose bottom layer has been exposed to acid for different durations of time. As rust formation in the metal is a voltaic phenomenon, it would mean that the acid corrosion of the bottom layer would adversely affect the top layer of the substrate. Consequentially, droplet motion and the droplet’s contour would change in different corrosive scenarios which we could then detect with novel parameters in our lab. One such parameter is the Interfacial Modulus (GS), which describes the initial resistance of the solid’s outer layer towards the liquid. We can understand this parameter with the aid of the novel device, known as the Centrifugal Adhesion Balance (CAB). As we cause the drop to slide across the substrate at constant normal force condition, we observe the difference in the contour of the drop as it slides across the substrate. The real-time change in contact angles at each edge of the drop, along with its change in external lateral force, causes a change in the GS values, which varies in different corrosive scenarios.